Conceptual model of game aesthetics for perceived learning in narrative games - Abu Bakar, Juliana Aida; Ahmad, Mohd Khairie; Zulkifli, Abdul Nasir; Bahrin, Abdul Syafiq (2016)
Narrative games may offer reasoning on players' behavior or make-believe on players' personation as a pursuit to achieve specific goals.One of the goals is probably the intention to instill learning, which subconsciously provide information on the content of the game.However, there is lack of empirical evidence on game aesthetics for player's perceived learning.By means of expert review, this article reports on conceptual model of game aesthetics towards perceived learning and the degree of importance of each attributes in perceived learning.Findings reveal that all experts agreed on the relationship between game aesthetics and perceived learning. However, expert recommends three other conditions that may contribute to learning: player's motivation, learning content, and game splay.Future work will continue to design and develop the game prototype and to investigate the relationship between game aesthetics and perceived learning.